The Identification Of Squillid Mantis Shrimp And Preliminary Study On Reproduction And Larviculture Of Oratosquillina Interrupta Found In Penang Waters - Lee, Li Yen (2023)
Stomatopods or mantis shrimps were historically sold as cheap by-catches. Presently, with increased economic importance in various countries and it is commercially captured for its unique taste and texture. Mantis shrimp has a potential for local aquaculture practices. This study focuses on assessing optimal breeding protocol and determination of larval developmental stages, particularly for the mantis shrimp Oratosquillina interrupta